Tantangan Program Tahfidzul Qur’an Berbasis Online di Masa Pandemi Covid 19 - Hanifiyah, Fitriyatul; Hidayah, Anis Rofi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
The world has been shocked by the outbreak of a virus called Corona or often referred to as Covid-19 (Corona Virus Diseases-19). This virus began to endemic for the first time in Wuhan City, the capital of China's Hubei Province and the transmission of this virus spread very quickly throughout the world, including Indonesia. The Corona outbreak has greatly affected all sectors, both in the economic, social and educational sectors. The impact of this Corona virus pandemic in the field of Education is very significant. This is evidenced by the totality of changes in the learning process or teaching and learning activities both in institutions and non-formal. In non-formal institutions, the impact of the pandemic occurred, one of which was in institutions that held the Tahfidzul Qur'an program. The learning process of the program must also adapt to the conditions that occurred during the COVID-19 pandemic, namely the online teaching and learning process, in this case via the Whatsapp application. This study uses a qualitative approach with the type of literature Library Research while the method used is descriptive. The results of this study indicate that the learning problems of the Tahfidzul Qur'an program occur during a pandemic which includes the limitations of internet access that occur in certain areas, signal services that are also not maximized, limited mastery of technology media experienced by some teachers and students as well as management less efficient and good time. This problem resulted in decreased morale, laziness, and boredom for students who took part in the program.